Mindfulness and Burnout in Elite Junior Athletes: The Mediating Role of Experiential Avoidance - Zhang, C.; Si, G.; Chung, P.; Gucciardi, Daniel (Routledge, 2016)
Previous research suggests that mindfulness and experiential avoidance are negatively and positively related to athlete burnout, respectively. It is unknown, however, whether experiential avoidance functions as a mediator between mindfulness and athlete burnout. To address this gap, 387 elite Chinese junior athletes (M = 15.44 years, SD = 1.42) completed self-report measures of mindfulness, experiential avoidance, and athlete burnout. Findings provided cross-sectional evidence that experiential avoidance mediated the inverse association from mindfulness to each of the three burnout dimensions. No gender difference of these indirect effects was revealed. This study is the first to test the theoretical sequence in which mindfulness is associated with athlete burnout via experiential avoidance and provide additional support the adaptive nature of mindfulness.